2006
DOI: 10.3123/jemsge.28.31
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Genotoxicity of Kojic Acid by Mutagenicity in Salmonella and Micronucleus Induction in Rodent Liver

Abstract: Three lots of kojic acid (KA) which were produced for use as a reagent, food additive and in cosmetics were shown to be mutagenic in S. typhimurium TA100 with or without S9 mix, with a speciˆc activity of around 100 revertants per mg of KA. Since there are contradictory reports on genotoxicity of KA, we examined, using HPLC, whether the mutagenicity to S. typhimurium is due to KA itself, or due to contaminants present in the KA samples. Although two UV absorbing fractions were separated by HPLC, mutagenicity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The mutagenicity of kojic acid was studied in S typhimurium strain TA 100, with and without S9. 77 To rule out the possibility that mutagenicity observed in earlier studies was due to contaminants in kojic acid samples, the researchers purified 3 samples of kojic acid (reagent, food additive, and cosmetic lots) by high-performance liquid chromatography (HPLC) and tested the resulting fractions. In the mutation assay, kojic acid was tested at 500, 1000, and 1500 mg/plate.…”
Section: Bacterial Assaysmentioning
confidence: 99%
“…The mutagenicity of kojic acid was studied in S typhimurium strain TA 100, with and without S9. 77 To rule out the possibility that mutagenicity observed in earlier studies was due to contaminants in kojic acid samples, the researchers purified 3 samples of kojic acid (reagent, food additive, and cosmetic lots) by high-performance liquid chromatography (HPLC) and tested the resulting fractions. In the mutation assay, kojic acid was tested at 500, 1000, and 1500 mg/plate.…”
Section: Bacterial Assaysmentioning
confidence: 99%
“…Nohynek et al (14) demonstrated that kojic acid was mutagenic in S. typhimurium TA 98, TA 100, TA 1535, TA102 and E. coli WP2uvrA, but not in TA 1537 by the standard Ames test. Ishikawa et al (15) demonstrated that three diŠerent lots of samples of kojic acid were mutagenic in S. typhimurium TA100 and their mutagenicities were derived from kojic acid itself, but not from any contaminants. In mammalian cell systems, kojic acid induced chromosome aberrations and sister chromatid exchanges in Chinese hamster ovary CHO cells with and without S9 mix (10).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it would be premature to conclude that its hepatic genotoxicity detected by the comet assay in both species contradicts to negative responses in the two-step carcinogenicity studies with both species. In our previous study, kojic acid induced micronuclei in regenerating liver of partially hepatectomized mice (9). Considering our previous observation that the comet assay-detectable DNA lesions can form chromosome aberrations in human lymphoblastoid WTK1 cells (10), it is interesting that both comet assay-detectable DNA damage and micronuclei were induced in mouse liver, which is a possible target organ of kojic acid carcinogenicity.…”
Section: Discussionmentioning
confidence: 91%
“…These facts suggest the possibility that kojic acid acts on hepatocytes as an initiator in mice and leads to the induction of hepatocelluar tumors. Although kojic acid induced micronuclei in the liver of regenerating mouse liver (9), no micronuclei were observed in regenerating rat liver and infant rat liver without partial hepatectomy (15).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation